142 The Efficacy of Written Symptom Questionnaires for the Management of Erectile Dysfunction. Issue 1 (1st April 2022) - Bhalla, R; Loucks, B; Comola, G; Johnsen, N
ABSTRACT: Introduction: The use of written screening tools and symptom questionnaires within the field of urology is widespread. Urologists regularly utilize such tools to help navigate preoperative counseling, understand the severity of a patient's symptoms, and guide clinical management. Self-administered screening questionnaires however require a baseline level of health literacy and comprehension in order for the results to be considered reliable. Prior work has shown that patient education and health literacy levels significantly impact the results of self-administered American Urological Association (AUA) symptom index questionnaire, which results in misclassification of voiding symptoms and potentially limits access to appropriate care. The International Index for Erectile Function (IIEF-5) is a previously validated self-administered questionnaire that is used to assess a patient's current erectile function. We hypothesize that men with lower health literacy and lower education levels are more likely to demonstrate a decreased understanding of the IIEF-5 and increased rates of symptom misclassification. Objective: The aim of our project is to assess the frequency of poor understanding of the IIEF-5 and to determine if patient education and health literacy impact self-administered versus verbally administered IIEF-5 questionnaires. Methods: In this pilot study, we prospectively enrolled consecutive, literate, English-speaking patients seen in an academic urology clinic for various complaints. Patients completed a self-administered, written IIEF-5 questionnaire per standard clinic protocol, and were subsequently re-administered the same IIEF-5 questionnaire verbally by a single trained researcher. The researcher answered patient questions and clarified questionnaire items as needed, as well as obtained basic demographic information related to education, health literacy, and race. Responses were compared by calculating the change in overall IIEF-5 scores between written and verbally administered instruments. Health literacy was determined utilizing the Brief Health Literacy Screen (BHLS), a validated health literacy tool. Results: A total of one hundred consecutive men were enrolled into this pilot study. The population was primarily Caucasian (83%) with 76% of men having some form of college education or higher level education. The median written IIEF-5 was 14 (IQR: 5, 23) while the median verbal IIEF-5 was 14 (IQR: 5, 23), p=1.00. The median delta IIEF-5 was 0 (IQR: -2, 0). The median BHLS was 14 (IQR: 12, 15). On multivariable model evaluating for the impact of BHLS and education level on delta IIEF-5 while adjusting for age, education level, and race, BHLS (p=0.09) and education level (p=0.23) were not significant. Conclusions: In this pilot study, there was no significant variance in overall scores when comparing the written to verbally administered IIEF-5 questionnaire. In contrast to prior studies evaluating the efficacy of other urologic symptom questionnaires, BHLS and education level were not significantly associated with changes in overall IIEF-5 scores. Disclosure: No